Decomposition of Fe3S above 250 GPa. Issue 18 (20th September 2013) - Ozawa, Haruka; Hirose, Kei; Suzuki, Toshihiro; Ohishi, Yasuo; Hirao, Naohisa
<x xml:space="preserve">Abstract</x> [1] We have determined subsolidus phase relations in the Fe–FeS system up to 271 GPa using laser‐heated diamond‐anvil cell techniques. In situ synchrotron X‐ray diffraction (XRD) measurements performed at high pressure and high temperature demonstrate the coexistence of hexagonal close‐packed (hcp) Fe and tetragonal Fe3S up to 241 GPa and 2510 K. In contrast, the XRD data obtained above 250 GPa show that the hcp phase coexists with the CsCl (B2)‐type phase for three different Fe–S bulk compositions (10, 16, and 20 atm% S). Furthermore, chemical analyses using a scanning transmission electron microscope on a retrieved sample indicate that Fe3S sample decomposes into two phases at 271 GPa and 2530 K, consistent with the XRD data. Theory predicts the presence of extensive solid solution between Fe and FeS at inner core conditions, whereas our results suggest that the Fe–FeS system remains eutectic at least to 271 GPa.